Effect of Holding Time and Cooling Medium on Microstructure and Hardness of AISI 8655 in Hardening Process - Alvian Toto Wibisono; Mavindra Ramadhani; Rochman Rochiem (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
The microstructure transformation of AISI 8655, affecting to hardness and impact properties in various hardening processes, has been investigated in this work. AISI 8655 specimens which had been prepared before hardening processes were heated to austenite temperature and held for 30 minutes and 60 minutes then continued by rapid cooling in various medium (air, oil and water). The hardened steel specimens were tested by optical microscope to observe microstructure, brinell test and impact test respectively to measure hardness and impact strength properties. Martensite and bainite were microstructures that appeared after hardening processes. The holding time for 30 minutes gave higher hardness properties than the holding time for 60 minutes. However, the holding time for 60 minutes performed higher impact strength than that for 30 minutes. The highest of hardness was performed by the specimen cooled in water medium at 552 BHN and the highest of impact strength was performed by the specimen cooled in air medium at 7.2 J/mm2.